Optimization of Energy Efficiency in Amine Regeneration Using a Novel Side Draw Flow Modification Method - Najib Meftah Almukhtar Omar; Abtesam Aboljam; Muhend Milad; Ruqaia Abuajil Sheliqa (African Journal of Advanced Pure and Applied Sciences, 2025)
Optimizing energy efficiency in gas-sweetening processes is crucial for reducing operational costs and improving environmental sustainability. This study introduces a novel approach to optimize the amine regeneration process, a critical component of gas sweetening operations, at the Mellitah gas plant. Using Aspen HYSYS software, a simulation model was developed and validated against actual plant data, achieving an absolute error of less than 1%, thereby confirming its accuracy. The optimization strategy is based on an innovative modification of the process flowsheet by incorporating a side draw stream on Tray 12, with flow rates ranging from 1000 to 6000 kgmol/h. New equipment, a heat exchanger (HX-101), and a flash separator (V-102) were integrated into the gas-sweetening process to enhance efficiency. HX-101 effectively reduced carbon dioxide (CO₂) concentration in the liquid side draw, while V-102 facilitated efficient phase separation. Analysis of side draw flow rates demonstrated significant energy savings. At a side draw flow rate of 6000 kgmol/h, the reboiler duty was reduced by 18% and the condenser duty by 5%. Additionally, increasing the side draw flow rate showed further potential for energy savings. These findings highlight the feasibility and effectiveness of this novel process modification, which is recommended for implementation at the Mellitah gas plant. This innovative optimization reduces energy consumption and operational costs and enhances the overall efficiency and sustainability of the amine regeneration process in gas sweetening operations.